2017
DOI: 10.1155/2017/9078598
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Electromagnetic Models of High‐Speed Solenoid Valve for Common Rail Injector

Abstract: A novel formula easily applied with high precision is proposed in this paper to fit the -curve of soft magnetic materials, and it is validated by comparison with predicted and experimental results. It can accurately describe the nonlinear magnetization process and magnetic saturation characteristics of soft magnetic materials. Based on the electromagnetic transient coupling principle, an electromagnetic mathematical model of a high-speed solenoid valve (HSV) is developed in Fortran language that takes the satu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Hung and Lim [12] presented a simulation study to improve the electromagnetic force of a solenoid injector, in which they changed the cross-sectional shape of the coil, thickness of the cut-off of the sleeve, and the relative position between the coil and plunger to obtain the highest electromagnetic force. The improvements of electromagnetic force based on the effects of structural parameters were also found in other studies [13][14][15][16][17][18][19][20][21][22]. The previous studies [2,[9][10][11][12][13][14][15][16][17][18][19][20][21][22] provided useful information when improving electromagnetic force in a solenoid by optimizing design parameters such as plunger shape, plunger mass, coil shape, coil turns, coil location, air gap, pole radius, and yoke thickness of the magnet.…”
Section: Introductionsupporting
confidence: 58%
“…Hung and Lim [12] presented a simulation study to improve the electromagnetic force of a solenoid injector, in which they changed the cross-sectional shape of the coil, thickness of the cut-off of the sleeve, and the relative position between the coil and plunger to obtain the highest electromagnetic force. The improvements of electromagnetic force based on the effects of structural parameters were also found in other studies [13][14][15][16][17][18][19][20][21][22]. The previous studies [2,[9][10][11][12][13][14][15][16][17][18][19][20][21][22] provided useful information when improving electromagnetic force in a solenoid by optimizing design parameters such as plunger shape, plunger mass, coil shape, coil turns, coil location, air gap, pole radius, and yoke thickness of the magnet.…”
Section: Introductionsupporting
confidence: 58%
“…An electromagnetic mathematical model of a high-speed solenoid valve was developed in Fortran language. Jianhui Zhao et al [15] discovered that the electromagnetic energy conversion characteristics of the HSV were affected by the drive current and the total reluctance, consisting of the gap reluctance and the reluctance of the iron core and armature soft magnetic materials. Paul D. Walker et al [16] established mathematical models of the integrated electrohydraulic solenoid valve and wet clutch piston assembly in the Simulink environment of Matlab.…”
Section: Introductionmentioning
confidence: 99%
“…The operating performance of the EPR depends on electromagnetic force of the solenoid valve. The previous studies concentrated on improving the electromagnetic force of solenoids based examination of structural parameters [5][6][7][8][9][10][11][12]. Hung et al [5] ISSN: 2734-9373 https://doi.org/10.51316/jst.152.ssad.2021.31.2.11 Received: December 23, 2020; accepted: May 13, 2021 developed a solenoid applied for a gas injector, in which they varied structural parameters such as plunger mass, spring stiffness, and coil turns to increase the electromagnetic force.…”
Section: Introduction *mentioning
confidence: 99%
“…Their results showed that the initial size of the fuel injector could be reduced by 35%, the attraction force increased by 26%, and the response time reduced by 76% by using the developed approach. Zhao et al [12] tested the effects of drive current and the air gap between the armature and iron core on the electromagnetic force of a highspeed solenoid valve in a common rail injector based on electromagnetic models. Their simulation results showed that when the air gap decreased, the electromagnetic force increased.…”
Section: Introduction *mentioning
confidence: 99%